Ecological Condition of the Territories of the Former Military Test Site and Public Health - KIBATAYEV, Kozy M.; SAKHANOVA, Svetlana K.; BASPAKOVA, Akmaral M.; UREKESHOV, Baktybergen S.; URGUSHBAYEVA, Gulnur M.; TUSSUPKALIYEVA, Kymbat Sh. (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020, 2020)
Nuclear explosions, radiation accidents and tests at military training grounds cause technogenic pollution of soil, water, plants, which affect not only the environment, but also have a negative impact on human health. The purpose of the research was to study the environmental status and morbidity of the population of the territory of the former military test site "Emba-5". Generally accepted methods were used to research the content of radionuclides and heavy metals in soil, water and plant products. A retrospective analysis of the morbidity and mortality of the population of the Mugalzhar district (for the period of 1995-2018) was performed. Samples of soil, water and vegetation of the "Emba-5" site revealed an increased content of copper, presence of heavy metals (zinc, lead, manganese) and technogenic radionuclides (Cs-137 and Sr-90). The gamma background level of the Emba-5 test site is higher than the regional average. Since 2007, there has been an increase in the incidence of neoplasia, since 2010, the incidence of haemopathy and diseases of blood-forming organs, iron deficiency anaemia and diseases of the circulatory system. Since 2000, there has been an increase in mortality from diseases of the respiratory system and since 2011 – from the digestive system diseases.